2018
DOI: 10.1080/09537104.2018.1431388
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the open canalicular system – the platelet’s specialized internal membrane network

Abstract: The open canalicular system (OCS) is an internal membrane structure found in platelets. First identified 50 years ago, the OCS comprises a tunneling network of surface-connected channels that appear to play an important role in platelet function. Yet, our understanding of how the OCS forms, how it functions, and what might regulate its structure and behavior remains fairly rudimentary. Structural abnormalities of the OCS are observed in some human platelet disorders. Yet, because platelets from these patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 46 publications
0
26
0
1
Order By: Relevance
“…Two rhinoceros species, white and black, have poorly developed OCSs (Du Plessis et al, ). The OCS is one of the major structures of human circulating platelets (Selvadori & Hamilton, ) and is described as playing an important role in endocytosis and secretions (Escolar, Lopez‐Vilchez, Diaz‐Ricart, White, & Galan, ), calcium concentration regulation (Davlouros, Xanthopoulou, Mparampoutis, Giannopoulos, Defterous, & Alexopoulos, ) and it communicates with the surrounding medium. Due to the absence of an OCS in bovine, equine and camel platelets, exocytosis have been reported to occur by direct fusion of the granules with the surface (Gader et al, ; Segura et al, ), and it is possible that a similar mechanism occurs in the platelets of other animals without an OCS.…”
Section: Resultsmentioning
confidence: 99%
“…Two rhinoceros species, white and black, have poorly developed OCSs (Du Plessis et al, ). The OCS is one of the major structures of human circulating platelets (Selvadori & Hamilton, ) and is described as playing an important role in endocytosis and secretions (Escolar, Lopez‐Vilchez, Diaz‐Ricart, White, & Galan, ), calcium concentration regulation (Davlouros, Xanthopoulou, Mparampoutis, Giannopoulos, Defterous, & Alexopoulos, ) and it communicates with the surrounding medium. Due to the absence of an OCS in bovine, equine and camel platelets, exocytosis have been reported to occur by direct fusion of the granules with the surface (Gader et al, ; Segura et al, ), and it is possible that a similar mechanism occurs in the platelets of other animals without an OCS.…”
Section: Resultsmentioning
confidence: 99%
“…As platelets also contain an OCS, receptor engagement and cytoskeletal rearrangement coordinates the exposure of this specialized internal membrane network that is important for protein transport (29) and amplification of prothrombotic responses. The cytoskeletal rearrangement enables platelet receptors to cluster (30,31) which amplifies signaling events and helps stabilize platelet contact points.…”
Section: Adheso-signaling Receptorsmentioning
confidence: 99%
“…In our ultrastructural characterization, we observed that in APP-PS1 mouse platelets, vacuolar and tubular structures occupy a significantly wider area of the cytoplasm in comparison to WT controls. We considered these structures as being part of the platelet OCS, a system of interconnected and tortuous membrane-bound channels that spans through the platelet interior (Rumbaut and Thiagarajan, 2010;White, 2013;Selvadurai and Hamilton, 2018). Further analysis using specific dyes for the OCS, such as ruthenium red (Heijnen and Korporaal, 2017;Selvadurai and Hamilton, 2018), or morphological characterization of platelets using 3D electron microscopy are needed to determine whether the structures we observed are, indeed, part of the platelet OCS.…”
Section: Alterations In the Ocs Of App-ps1 Mouse Plateletsmentioning
confidence: 99%
“…We considered these structures as being part of the platelet OCS, a system of interconnected and tortuous membrane-bound channels that spans through the platelet interior (Rumbaut and Thiagarajan, 2010;White, 2013;Selvadurai and Hamilton, 2018). Further analysis using specific dyes for the OCS, such as ruthenium red (Heijnen and Korporaal, 2017;Selvadurai and Hamilton, 2018), or morphological characterization of platelets using 3D electron microscopy are needed to determine whether the structures we observed are, indeed, part of the platelet OCS. Interestingly, abnormalities in platelet ultrastructure are common to other neurological disorders such as Parkinson's disease, where platelets display an enlarged OCS (Factor et al, 1994), amyotrophic lateral sclerosis (Shrivastava et al, 2011), or major depression (Mendoza-Sotelo et al, 2010).…”
Section: Alterations In the Ocs Of App-ps1 Mouse Plateletsmentioning
confidence: 99%